LARGE MAXILLARY RADICULAR CYST (CASE REPORT) - Panev, Dejan; Stojanova, Irena; Papakoca, Kiro; Markovska Arsovska, Mirjana; Spirov, Vanco (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
A cyst is defined as a pathological cavity lined by epithelium and the lumen is filled with cystic contents. Radicular cysts are most common odontogenic cysts and they are usually associated with carious, nonvital or fractured teeth. Many of them are usually asymptomatic and can be detected incidentally on routine radiography before the symptoms appear. Symptoms appeared when they are acutely inflamed. Radiologically, it arises from the apex of the root of a tooth and is bounded by a thin rim of cortical bone. The diagnosis of a cyst, in addition to clinical and paraclinical examinations must be confirmed by the histopathological findings. We present a case of a radicular cyst in the maxilla that exists a few years. 41 years old female patient has painless swelling that manifests extra-orally in the upper left buccal region. It has been recurring in recent years but the condition was improving with the administration of antibiotic therapy. Surgical treatment of the cyst (cystectomy in toto) with tooth extraction is the method of choice. Diagnosis and management of the patient are discussed. Keywords: odontogenic cyst, radicular cyst, maxilla, cystectomy in toto, histopathologic analysis